EFFICACY AND SAFETY OF PERCUTANEOUS TRANSTHORACIC NEEDLE ASPIRATION BIOPSY UNDER SOME LIMITATIONS: A PROSPECTIVE STUDY IN 109 PATIENTS - TANISARO, Komgrit; WEERAYACHAIYO, Wilaiwan; NIRAPATHAPONGPORN, Supranee; PEKANAN, Patchrin; KUMPOLPUNTH, Sopon (The ASEAN Journal of Radiology, 2023)
Percutaneous transthoracic needle biopsy was performed in 109 patients during April 1992 - April 1995. Diagnostic yield was slightly lower than the foreign reports due to different types of the needles used and the lack of immediate cytology reports. The incidence of hemoptysis was similar to other reports but the occurrence of the pneumothorax was less due to less repetition of the needle puncture. Considering socioeconomic and lack of medical-personnel-power in this country, this procedure as practised by us is quite practical.